STABILISASI TANAH LEMPUNG MENGGUNAKAN KERIKIL UNTUK MENINGKATKAN DAYA DUKUNG (CBR) DI LABORATORIUM SEBAGAI BAHAN TIMBUNAN - Annisaa Dwiretnani (Jurnal Talenta Sipil, 2018)
Clay is a type of soil that has a high shrinkage when the change in water content. Construction of roads built on clay soil often damaged, eg cracked or bumpy roads would be damaged so that road before reaching the age of the plan. This study analyzes the behavior of clay in the area of Mendalo Darat, Provinsi Jambi, get maximum soil density and optimum moisture content with the addition of gravel 10%, 20%, 30% and 40%, then tested in the from of nature of the soil, the California Bearing Ratio (CBR). The results, according to the Unified Soil Classification System (USCS) methods. The addition of gravel will cause the properties of the soil Liquid Limit (LL) decreased with Plastic Limit (PL) decreased so that the Plasticity Index (PI) decreased. The addition of gravel will be working actively on the CBR test. From the test results obtained, clay that is stabilized with gravel on variations of 10%, 20%, 30% and 40% indicate an increase in crayying capacity soil and significant decrease in plasticity index. On the gravel mixture of 40% there is significant increase in carrying capacity of 11,90% of power support for the original soil, and on the gravel mixture of 40% also decreased index plasticity of 1,21 % of the original soil plasticity index. The smaller the plasticity index, the carrying capacity is getting bigger.Keywords: clay, stabilized, CBR